Faktor Yang Mempengaruhi Kepatuhan Perempuan Usia Subur Dalam Deteksi Dini Ca Serviks - Lubis, Angela Ditauli; Pamilih, Ayu Trisni (Jurnal Borneo Cendekia, 2025)
Cervical cancer is the fourth most common cancer in women globally, with 64,000 new cases in 2020. In Indonesia, cervical cancer ranks second after breast cancer, with 36,633 cases accounting for 17.2% of all cancers in women. This case has a high mortality rate of 21,003 deaths accounting for 19.1% of all cancer deaths. The purpose of this study was to determine the factors that influence women's compliance with early detection of cervical cancer, including individual, social, and health service factors. This research is a quantitative research with analytical survey with cross sectional approach. Sampling using simple random sampling technique with a sample size of 112 respondents with inclusion criteria of women aged 25-50 years who have been married, willing to be respondents and can read and write well. Data analysis using descriptive frequency test, chi square test, and multiple logistic regression test. The results of this study obtained a relationship between age p value (0.000), education p value (0.104), occupation p value (0.002), parity p value (0.000), general health condition p value (0.018), distance to health facilities p value (0.006), knowledge p value (0.021), family support p value (0.011), and the role of health workers p value (0.000) with women's compliance with early detection of cervical cancer. The results of multiple logistic regression test obtained the most influential variable, namely age p value (0.045) with women's compliance with early detection of cervical cancer Based on statistical tests obtained the results of the most influential factor, namely age factor. The conclusion of this study is that it is hoped that this study can increase women's knowledge regarding cervical cancer screening.